2021
DOI: 10.1007/s11126-021-09884-0
|View full text |Cite
|
Sign up to set email alerts
|

Structured Evaluation of Rehabilitation Programs Outcomes in Psychiatry: Application of a Recovery-Centered Model

Abstract: Rehabilitation is oriented to psychiatric patients’ recovery through specific techniques and structured projects, not yet fully standardized, carried out in territorial services. This study aims to apply an operational structured outcome indicator model (hospitalizations, continuity of care, LAI treatment adherence, working support) through a recovery-centered model in a rehabilitation community in Milan. This observational-retrospective study included 111 patients from a University High Assistance Rehabilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…In Italy, the rate of employment among patients with severe mental illness ranges 75% to 90% (Vanzetto et al, 2021). Nonetheless, after the approval of the national law 68/99, the right to work for people with disability became mandatory and a set of recommendations regarding the job-placement of people affected by mental illness within the rehabilitation interventions of the national Departments of Mental Health has been released (Grillo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In Italy, the rate of employment among patients with severe mental illness ranges 75% to 90% (Vanzetto et al, 2021). Nonetheless, after the approval of the national law 68/99, the right to work for people with disability became mandatory and a set of recommendations regarding the job-placement of people affected by mental illness within the rehabilitation interventions of the national Departments of Mental Health has been released (Grillo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Few studies focused on the identification of efficient outcome measures. In a recent research, Vanzetto and colleagues identified (i) improvement in validated psychometric scales, (ii) reduction of hospitalizations, (iii) improved continuity of care, (iv) adherence to a long acting injectable (LAI) antipsychotic, and (v) a stable employment for at least 1 year after discharge as reliable outcome measures of improved global functioning ( 39 ). Another outcome measure often used in literature is the destination at discharge from the rehabilitation program, an indirect measure of global functioning that identifies if a patient can return to an independent living environment or needs further care.…”
Section: Introductionmentioning
confidence: 99%